Impact of COVID‐19 on the management and outcomes of ureteric stones in the UK: a multicentre retrospective study. (19th October 2022) - Byrne, Matthew H.V.; Georgiades, Fanourios; Light, Alexander; Lovegrove, Catherine E.; Dominic, Catherine; Rahman, Josephine; Kathiravelupillai, Senthooran; Klatte, Tobias; Saeb‐Parsy, Kasra; Kumar, Rajeev; Howles, Sarah; Stewart, Grant D.; et al.
Abstract : Objectives: To determine if management of ureteric stones in the UK changed during the coronavirus disease 2019 (COVID‐19) pandemic and whether this affected patient outcomes. Patients and methods: We conducted a multicentre retrospective study of adults with computed tomography‐confirmed ureteric stone disease at 39 UK hospitals during a pre‐pandemic period (23/3/2019–22/6/2019) and a period during the pandemic (the 3‐month period after the first severe acute respiratory syndrome coronavirus‐2 case at individual sites). The primary outcome was success of primary treatment modality, defined as no further treatment required for the index ureteric stone. Our study protocol was published prior to data collection. Results: A total of 3735 patients were included (pre‐pandemic 1956 patients; pandemic 1779 patients). Stone size was similar between groups ( P > 0.05). During the pandemic, patients had lower hospital admission rates (pre‐pandemic 54.0% vs pandemic 46.5%, P < 0.001), shorter mean length of stay (4.1 vs 3.3 days, P = 0.02), and higher rates of use of medical expulsive therapy (17.4% vs 25.4%, P < 0.001). In patients who received interventional management (pre‐pandemic 787 vs pandemic 685), rates of extracorporeal shockwave lithotripsy (22.7% vs 34.1%, P < 0.001) and nephrostomy were higher (7.1% vs 10.5%, P = 0.03); and rates of ureteroscopy (57.2% vs 47.5%, P < 0.001), stent insertion (68.4% vs 54.6%, P < 0.001), and general anaesthetic (92.2% vs 76.2%, P < 0.001) were lower. There was no difference in success of primary treatment modality between patient cohorts (pre‐pandemic 73.8% vs pandemic 76.1%, P = 0.11), nor when patients were stratified by treatment modality or stone size. Rates of operative complications, 30‐day mortality, and re‐admission and renal function at 6 months did not differ between the data collection periods. Conclusions: During the COVID‐19 pandemic, there were lower admission rates and fewer invasive procedures performed. Despite this, there were no differences in treatment success or outcomes. Our findings indicate that clinicians can safely adopt management strategies developed during the pandemic to treat more patients conservatively and in the community.